The Influence Of Promotion, Location And Service Quality On Purchase Decisions (Survey of consumers at Azad Store, in the Cihideung Tasikmalaya Shopping Area) - Rahmah, Amalia; Pauzy, Depy Muhamad; Irawan, Irly Artiara (Journal of Management, Economic, and Accounting, 2024)
In this research, we discuss the phenomenon of sales problems at the Azad Store, namely the discovery of the problem that the products sold each year experience a decline which has an impact on decreasing business income. consumer purchasing decisions. The purpose of this study was to determine the effect of promotion, location and quality of service on purchasing decisions at the Azad Store, in the Cihideung Tasikmalaya Shopping Area. The research method used is a quantitative method with a survey approach to 100 respondents who are consumers of Toko Azad. The types of data used are primary data and secondary data. The data analysis technique used is multiple regression analysis. The results of this test prove that promotion, location and service quality have a significant effect simultaneously or partially on consumer purchasing decisions at Azad Store, in the Cihideung Tasikmalaya Shopping Area.